Automatic food cover / Ahmad Safwan Ramli, Mohd Fildza Che Ibrahim and Muhamad Abdul Hakim Che Deraman - Ramli, Ahmad Safwan; Che Ibrahim, Mohd Fildza; Che Deraman, Muhamad Abdul Hakim (2012)
Our main purpose of this project is to construct and make a food cover that can produce heat that can make food inside it always warm. In order to make the food inside food cover always warm we have to produce a uniform temperature inside the food cover. To produce a. uniform temperature we combine three different circuit that is heater circuit, heat sensor circuit and comparator circuit. We use the heater circuit as the element of heating for our project. Then, we use heat detector circuit to detect to temperature of the environment in the food cover. The comparator circuit act as the automatic for our project. When the heat detector sense the heat that we set is enough, so the comparator will switch off the heater circuit. Then other situation when the heat sense by heat detector is not enough the comparator will switch on the heater circuit.